Do Sertão ao território das Minas e das Gerais: entradas e bandeiras, política territorial e formação espacial no período colonial - Patricio Aureliano Silva Carneiro (2013)
One of the most significant challenges in the historical studies lies in the incorporation and analysis of spatial processes andterritorial elements which influence temporality and events, as well as fashion and organize space in the past. The present thesis aims at emphasizing the importance of such relation as well as the connections between space and time, history andgeography. First, based on Anglo-Saxon bibliography, we review the conceptual and methodological aspects of historical geography, discuss this field of studies origins, the conceptual organization, the most prominent scholars contributions along with the new trends and challenges of this subject. Then, we use methods and concepts of historical geography to study the territorial and regional formation of the Captaincy of Minas Gerais in the colonial period. We created a historical-geographical perspective of this jurisdictions constitution, using occupationand territorial organizationas guidelines for the investigation. The main inquiry was the next: whats the importance of space in the new areas conquest and occupation and of the territorial structures implemented by the metropolis to facilitate the colonization and guarantee the transformation of mines and backwoods into the colonial territory? In answer to that question, we verify the hypothesis of that the understanding of territoriality forming of Minas Gerais is more enrich with the integration ofgeographical categories that allude to relations space-time. Based on this integration, we try to show the importance of geographical landmarks and of the territorial politics in the occupation and formation of the captaincy and in the early internal distinction of his space, as well like the manifestation of the otherness between the settlers to stand up to installation of the metropolitan power. This study begins with the interior exploration journeys (entradasand bandeiras), later first half of the 16th century, and finish in mid-19th century, context of provinces structural change. The investigation is based in the consultation and analysis of numerous documents found in several archives, institutions and journals, travelers reports, bibliographical reviews and observations of the landscape.